A New Approach to the Endogenous Correction of Interregional Income Disparity: Extended Interregional IO by Trading Biomass CO₂ Credit - Ryohei Nakamura (European Regional Science Association (ERSA), 2013)
In this study we develop a new approach to correct interregional income disparity endogenously by extending traditional interregional IO table. The meaning of enew approachf is that to propose a new concept for correcting interregional income disparity by utilizing environmental resources which are usually abundant in rural regions and to conduct new type of simulation which implies a change of input structure induced by energy substitution. We use 11 interregional IO table which is extended from 9 interregional IO table developed METI (Ministry of Economy, Trade, and Industry) in Japan. By implementing new type of simulation we can find substantial improvement of income disparities between metropolitan areas and rural regions by trading CO2 credit as well as trading renewable energy such as wooden biomass chips and pellets. Therefore, we should promote renewable energy using rural environmental resources to vitalize rural economies, and it will result in endogenous correction of interregional economic disparities.
Keywords: 330; Interregional IO; Wood Biomass; interregional Income Disparity; endogenous development; CO2 Credit; Export Biomass